Effects of GPA, gender, and economic support on prospective biology teachers’ TPACK across two methods - Zakiyati Salma; Muhyiatul Fadilah; Linda Advinda; Heffi Alberida; Ahmad Adnan Mohd Shukri (University of Muhammadiyah Malang, 2026)
Background: Technological pedagogical and content knowledge (TPACK) is commonly measured using self-report questionnaires, although such scores may not fully represent prospective teachers’ demonstrated capacity to integrate technology, pedagogy, and biology content. Objective: This study examined the effects of gender, economic support, and grade point averages (GPAs) in content, pedagogy, and technology courses on prospective biology teachers’ TPACK and compared results obtained from self-report and performance-based assessment. Methods: A quantitative correlational design involved 100 biology education students from the 2021–2023 cohorts at Universitas Negeri Padang, selected through proportionate stratified random sampling. TPACK was measured using a 28-item questionnaire and an integrated performance-based assessment comprising 13 CoRe prompts and 11 PaP-eRs prompts. Multiple linear regression was conducted separately for each assessment method, and a paired-samples t-test compared the two scores. Results: The questionnaire score (M = 83.57, SD = 3.26) was significantly higher than the CoRe–PaP-eRs score (M = 67.11, SD = 4.01), with a mean difference of 16.46 points, t(99) = 37.78, p < .001. For the questionnaire, economic support and technology-course GPA were significant predictors. For CoRe–PaP-eRs, economic support, pedagogy-course GPA, and technology-course GPA were significant predictors, whereas gender and content-course GPA were not significant in either model. Conclusion: Self-reported TPACK and demonstrated TPACK yield systematically different profiles. Combining both methods provides a more defensible diagnosis of prospective teachers perceived competence and their ability to enact integrated knowledge in instructional planning.